ANALYSIS OF ORNAMENTAL FISH CULTIVATION IN SIMPANG TIGA VILLAGE BUKIT RAYA DISTRICTS CITY PEKANBARU RIAU PROVINCE - Putra, Aldi Erman; Amrifo, Viktor; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research on the cultivation of ornamental fish in Kelurahana Simpang Tiga was held in January 2016, ornamental fish breeding place in the village of Simpang Tiga subdistrict Bukit Raya Pekanbaru in Riau province. The purpose of this study was to determine the investments, the net income and the feasibility of cultivation of ornamental fish. The method used is the method of determination of the survey respondents were census. Respondents are drawn is the overall ornamental fish farmers who grow ornamental fish, amounting to 4 respondent. The results of the research effort buddidaya menjukan that ornamental fish farmers in the village of Simpang Tiga with total investment ranging between Rp.8.933.800 until Rp.11.641.800, net revenues received by farmers for harvest once every three months ranged between Rp.5.291. 402 up to Rp.7.270.989, based on investment criteria then obtained RCR ranges - RCR ranged from 2.35 to 2.82, FRR ranged between 52% - 72%, PPC ranged from -2.04 to 1.57. From these data show that the cultivation of ornamental fish in Kelurah Simpang Tiga is appropriate to proceed and have a very favorable prospects.Key word: Cultivators, Investment, Net Income, Level Eligibility